Resilience, Sustainability and Transformability of Cities as Complex Adaptive Systems. - Olazabal, Marta (Springer Fachmedien, 2017)
Cities can be understood as complex-adaptive systems that have the opportunity to manage their resilience towards sustainability through processes of transformation. The concept of "urban resilience" has been applied in many different disciplines (climate change, disaster risk reduction, planning, economy, sociology and psychology) which enrich the study of its tenets. Yet there is a lack of a shared framework, of a widely accepted definition and a lack of an operative approach to urban resilience. In addition to this, the concept of "transformation" has been discussed and used in the study of different types of systems such as socio-technical systems (STS) and socio-ecological systems (SES). In this chapter the "umbrella" concept of "Sustainable Urban Transformation" (SUT) and the specific notion of "Urban Resilient Sustainability Transition" (URST) are proposed to provide a conceptual framework for resilience and transformability and answer the question of how cities should plan and manage their processes of change towards sustainability. Further, three challenges are identified: investing in technology, grey and green infrastructures; understanding institutions and actors in SUT; and fostering knowledge generation and management for enabling urban resilient sustainability transitions.
Keywords: Stadt; Resilienz; Vulnerabilität; Transformation; Nachhaltigkeit; Stadtentwicklung; Konzeption; Stadtsystem; Komplexität; Anpassung; Infrastrukturinvestition; Akteur; Stadtmanagement